2005
DOI: 10.1126/science.1112915
|View full text |Cite
|
Sign up to set email alerts
|

DISC1 and PDE4B Are Interacting Genetic Factors in Schizophrenia That Regulate cAMP Signaling

Abstract: The disrupted in schizophrenia 1 (DISC1) gene is a candidate susceptibility factor for schizophrenia, but its mechanistic role in the disorder is unknown. Here we report that the gene encoding phosphodiesterase 4B (PDE4B) is disrupted by a balanced translocation in a subject diagnosed with schizophrenia and a relative with chronic psychiatric illness. The PDEs inactivate adenosine 3',5'-monophosphate (cAMP), a second messenger implicated in learning, memory, and mood. We show that DISC1 interacts with the UCR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
589
4
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 603 publications
(613 citation statements)
references
References 21 publications
18
589
4
2
Order By: Relevance
“…Using mice deficient in PDE4B, it has been demonstrated that this subtype plays a critical role in lipopolysaccharide-induced signaling and inflammatory responses (Ariga et al, 2004;Jin et al, 2005a). Most recently, it has been shown that PDE4B is required for the antipsychotic effect of rolipram (Siuciak et al, 2007), which is consistent with the association of this subtype with schizophrenia (Millar et al, 2005). Nevertheless, little is known about the CNS function of PDE4B.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Using mice deficient in PDE4B, it has been demonstrated that this subtype plays a critical role in lipopolysaccharide-induced signaling and inflammatory responses (Ariga et al, 2004;Jin et al, 2005a). Most recently, it has been shown that PDE4B is required for the antipsychotic effect of rolipram (Siuciak et al, 2007), which is consistent with the association of this subtype with schizophrenia (Millar et al, 2005). Nevertheless, little is known about the CNS function of PDE4B.…”
Section: Discussionmentioning
confidence: 82%
“…While the roles of these variants are still not known, recent studies using mice deficient in PDE4B have shown that this subfamily plays a complementary role in the control of neutrophil function (Ariga et al, 2004) and is required for antipsychotic effects of rolipram (Siuciak et al, 2007). In addition, PDE4B also is involved in schizophrenia by interacting with the DISC1 gene, a candidate susceptibility factor for schizophrenia (Clapcote et al, 2007;Millar et al, 2005). These results indicate that PDE4B plays a significant role in CNS functions.…”
Section: Introductionmentioning
confidence: 99%
“…Haploinsufficiency has been proposed owing to the decreased expression of full-length DISC1 and the failure to detect mutant DISC1 in lymphoblastoid cell lines derived from the patients. 31 However, the available data do not completely rule out the production of mutant DISC1. It is uncertain to what extent lymphoblast expression mirrors brain expression.…”
Section: Introductionmentioning
confidence: 98%
“…[28][29][30] In addition, alterations in the interaction of DISC1 with phosphodiesterase 4B have been suggested to contribute to the pathogenesis of major mental disorders. 31 Possible outcomes of the translocation in the DISC1 gene include haploinsufficiency or the production of a mutant-truncated DISC1 protein. Haploinsufficiency has been proposed owing to the decreased expression of full-length DISC1 and the failure to detect mutant DISC1 in lymphoblastoid cell lines derived from the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a possible role of increased cAMP PDE activity in the etiology of schizophrenia has been recently suggested. Millar et al (2005) show that the disrupted in schizophrenia 1 (DISC 1) protein normally sequesters PDE4 (inhibiting activity); thus, a loss of DISC1 could result in increased PDE4 activity. To determine if decreased cAMP signaling is responsible for the effect of Gas* on PPI, we measured cAMP levels and cAMP PDE activity across several brain regions in these transgenic mice.…”
Section: Introductionmentioning
confidence: 99%